EDUKASI MENABUNG MELALUI SEMINAR INTERAKTIF BERBASIS BERMAIN, CERITA DAN PRAKTIK PADA ANAK USIA DINI DI DESA CISIMEUT RAYA - Dwisapto Yusuf Pradana; Yeni Khoirunnisa Agustiani; Fat'Chatus Chanifa Jikhan; Muhammad Lukman Hakim (SEBA: Jurnal Pengabdian kepada Masyarakat, 2026)
The low understanding of early childhood children regarding the concept of saving in rural areas is a problem that needs to be addressed through planned educational approaches appropriate to the child's developmental stage. This community service activity was carried out as part of the Student Community Service (KKM) program at PAUD Al-Fatha, Cisimeut Raya Village, Leuwidamar District, Lebak Regency, Banten Province, with the aim of instilling saving awareness and motivation from an early age in preschool-aged children. The method used was an integrated combination of play, storytelling, and direct practice. The implementation was divided into three stages: preparation, interactive seminar, and evaluation. During the seminar, children were engaged in a simulation, listened to a short story conveying the value of saving, and practiced saving directly using a piggy bank which they then brought home as a tool for daily habituation. The results showed that children responded enthusiastically to all activities, and the combined method proved effective in conveying the message about the importance of saving in a fun and memorable way. PAUD teachers and parents were also involved to ensure the continuation of saving habits after the program ended. This program demonstrates that basic financial literacy education can be implemented from an early age through creative approaches without requiring complex facilities, and has potential to be replicated in other PAUD institutions in rural areas. Keywords: Early Childhood Education, Saving Education, Financial Literacy, Saving Habits